What makes an image worth a thousand words? Teaching strategic visual analysis and synthesis via semiotics. Issue 2 (3rd April 2021) - Durrani, Sameera
Abstract : Courses : Visual Rhetoric, Visual Communication, Multiplatform Journalism, Advertising, Journalism, Public Relations. Objective : This unit activity requires that students analyze and produce imagery with the help of semiotic theory. Students will (1) learn to connect theory with practice holistically by simultaneously practicing visual analysis and synthesis; (2) practice visual rhetoric, a key skill for professionals from media and related sectors; and (3) understand the basics of visual storytelling.